2006
DOI: 10.1007/s00264-006-0202-z
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive Oxford medial unicompartmental knee arthroplasty

Abstract: We present the peak outcome results of the Oxford medial unicompartmental arthroplasty through a minimally invasive ssurgical incision. This prospective study included 78 Oxford medial unicompartmental knee replacements in 68 patients. At the 2 year review the patients achieved a mean Oxford Knee Score of 38.3. This was not significantly different to the 2 year results of the phase 2 Oxford knee carried out using a standard parapatellar approach when patients achieved a mean OKS of 36.0. Four unicompartmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 15 publications
5
29
0
Order By: Relevance
“…This rate is comparable with the results using the single peg cemented implant from the originating centre reported by Pandit [1] and an independent centre reported by Svärd [2,13]. This outcome is better than our previous results using the cemented single peg implant [5,6] and the nine years survival rate of 89% reported in the National Joint Registry of England, Wales and Northern Ireland (NJR) or survival rates from other national joint registers [4,14]. The survival rate was highest when carried out for the patients who satisfied the original recommended indications for the Oxford knee: anteromedial osteoarthritis (AMOA) [8].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This rate is comparable with the results using the single peg cemented implant from the originating centre reported by Pandit [1] and an independent centre reported by Svärd [2,13]. This outcome is better than our previous results using the cemented single peg implant [5,6] and the nine years survival rate of 89% reported in the National Joint Registry of England, Wales and Northern Ireland (NJR) or survival rates from other national joint registers [4,14]. The survival rate was highest when carried out for the patients who satisfied the original recommended indications for the Oxford knee: anteromedial osteoarthritis (AMOA) [8].…”
Section: Discussionsupporting
confidence: 89%
“…The main weakness of this study is the lack of a contemporaneous control group of patients because we stopped using the single peg version in 2003 as a result of our observation of loosening [5,6]. During the last 10 years, as mentioned earlier, we have no doubt gained a better understanding of technical factors during surgery which may well have contributed to improved results.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this finding applies only to deviations reported in our patient population after a relatively short follow-up period of four to seven years. In the long term, deviant implant positions (i.e., if impingement occurs) may lead to increased polyethylene wear and may result in implant failure [6,15,27,28,32,33]. Therefore, long-term studies are necessary to define evidence-based tolerance limits for implant positions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that UKA is a viable option for the treatment of unicompartmental osteoarthritis and some authors have also even reported excellent outcomes, focusing attention on careful patient selection and correct indications [1,3,9,17,20,26]. Advantages of UKA compared to total knee arthroplasty (TKA) are cost-effectiveness, fewer serious complications [21,24] and better postoperative functional outcome [9,27].…”
Section: Introductionmentioning
confidence: 99%